And then there were six: a revision of the genus Phanolinopsis Scheerpeltz (Coleoptera: Staphylinidae: Staphylininae) - Chatzimanolis, Stylianos (Zootaxa, 2017)
The previously monotypic genus Phanolinopsis Scheerpeltz is revised and four species are described as new: Phanolinopsis erythros sp. n. from Guatemala and Panama, Phanolinopsis goniakos sp. n. from Costa Rica, Phanolinopsis metaksenios sp. n. from Costa Rica and Panama, and Phanolinopsis norahae sp. n. from Colombia and Ecuador. Torobus fassli (Bernhauer) is transferred to Phanolinopsis as Phanolinopsis fassli comb. n. Detailed morphological illustrations and a key is provided for the identification of the species.